Identifikasi Potensi dan Ancaman Eco-tourism Kecamatan Biduk Biduk Kabupaten Berau Provinsi Kalimantan Timur - Dadang Ilham Kurniawan Mujiono; Kurnianto Rombe Rante; Rivaldi Nasution (Jurnal Pariwisata Terapan, 2019)
Indonesia famous throughout the world as archipelago state followed with tropical climate, as a result this country is full with magnificent natural tourism. One of extraordinary tourist attraction is Indonesia’s underwater world, and one them located in East Kalimantan Province. Despite the fame of natural resources, this province also providing remarkable natural attraction, especially Berau District, precisly in Biduk Biduk Sub-District. Although this area own magnificent tourist attraction, yet the area is experiencing numerous challenges and threat. In terms of research methodology, this scientific paper adopt descriptive analyze which describe the natural tourism potency and analyze the challenges and threats associated with tourist attraction in Biduk Biduk sub-district. Moreover, the type of data classified as primer data, where the author conducting field research in Biduk Biduk sub-district through direct observation, in-depth interview and collect the data in associate institutions. The result shows that natural tourism in Biduk Biduk sub-district can divided into two categories, and those are land based and sea based. Furthermore, possible obstacles which experienced by this area are related with the plan to open the coconut palm oil and the lack of promotion as well as the road infrastructures.